1986
DOI: 10.1159/000199380
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Hyperplasia of Gastrin and Enterochromaffin-Like Cells in the Stomach

Abstract: The stomach is rich in endocrine cells, most of which are still unidentified with respect to the peptide hormones they produce. The endocrine cell populations in the antrum usually differ from those in the oxyntic mucosa. Gastrin cells are found in the antrum and respond readily to stimuli from the gastric lumen, such as changes in the pH and the presence of food. In order to study the functional control of the antral gastrin cell, rats were subjected to different kinds of surgery. The serum gastrin concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 12 publications
3
48
0
Order By: Relevance
“…Nuclei contained prominent nucleoli and wellstained chromatin, but were otherwise unremarkable. These findings are consistent with those described for ECL cells in rats (20,22,26) and in man Although there were no carcinoid tumors at 55 mg/kg of BL-6341 or in the rats receiving the reference compound (cimetidine at 950 mglkg), proliferations of argyrophil endocrine cells could be detected in these groups at both 1 and 2 years by use of appropriate silver stains. At 1 year, the argyrophil endocrine cell increase was significantly greater than in controls at both 300 and 55 mg/kg of BL-6341 (Table 11).…”
Section: Two-year Ratsupporting
confidence: 90%
See 2 more Smart Citations
“…Nuclei contained prominent nucleoli and wellstained chromatin, but were otherwise unremarkable. These findings are consistent with those described for ECL cells in rats (20,22,26) and in man Although there were no carcinoid tumors at 55 mg/kg of BL-6341 or in the rats receiving the reference compound (cimetidine at 950 mglkg), proliferations of argyrophil endocrine cells could be detected in these groups at both 1 and 2 years by use of appropriate silver stains. At 1 year, the argyrophil endocrine cell increase was significantly greater than in controls at both 300 and 55 mg/kg of BL-6341 (Table 11).…”
Section: Two-year Ratsupporting
confidence: 90%
“…The results of these silver stains, especially the Sevier-Munger technique, suggested that the carcinoid tumors were composed of enterochromaffinlike (ECL) cells (20,22,23). The immunoperoxidase technique demonstrated the presence of histamine in the proliferated endocrine cells in the fundic mucosa.…”
Section: Two-year Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells seem to be regulated by gastrin, both with respect to activity, reflected in their capacity to produce and release histamine, and to rate of proliferation. 'After various types of surgical interventions in the stomach in the rat, leading to changes in the plasma levels of gastrin, a causal relationship between circulating gastrin levels and the density of ECL cells in the oxyntic mucosa was postulated by Hdkanson and coworkers (9). Such a relationship was also evident during omeprazole and ranitidine treatments (see below).…”
Section: General Tropliic Eflects Of Hypergastriiieniiamentioning
confidence: 95%
“…Their function is unknown, in the sense that the peptide hormone they produce has not yet been identified. However, the ECL cells are active in the production and storage of histamine and are known to be under the control of gastrin (9). Based on this knowledge, it is not surprising that long-term (2 years) treatment of rats with potent long-acting inhibitors ofgastric acid 267 (20 nmol x kg-I x hour-') and carbachol(l10 nmol x kg-l x hour-') for 2 hours.…”
mentioning
confidence: 99%